«Tutto che mi resta è gia perduto»: la influència de Salvatore Quasimodo en l'obra de Ponç Pons. - PEREIRA RUEDA, ANDREA (Scripta)
The aim of this work is to study the influence of Salvatore Quasimodo's poetry on Ponç Pons's literature. The work is divided into three parts. In the first, the literary influences of the Menorcan poet during his first poetic stage will be analysed. Despite not finding echoes of the Italian author, this section will serve to explain the origin of the vindication of his Menorcan identity, which is an aspect that links with the literature of Quasimodo. In the second and third part of the study, the influence of Quasimodo in the second and third literary stage of Ponç Pons will be analyzed. The analysis will therefore be diachronic and with a comparative perspective.